Indonesian Cyberbullying Issues: The Impoliteness in Communication - Nadhirah Muthi'ah; Umar Mono; Alemina Br. Perangin-Angin (Universitas Teuku Umar, 2022)
This paper is aimed at describing the cyberbullying issues that occur in social media platform especially in Instagram. The qualitative method is used in this paper. The data source is obtained from several Indonesian Celebrity Instagram accounts through case study approach. Through this paper, the researcher presents several examples of cyberbullying cases, what motives that cause someone to become a bully, and what are the impact that will occur in victims of bullying. By identifying and analysing all the data, the researcher found the motives of someone became a bully, such as; do not like the presence and personality of others, tends to saying negative comments which immoral and abusive, to entertain others by mocking someone, having bad personality such as envy, jealousy of someone’s achievements, having high of self-confident, think the bullies are better and more qualified than the victims and assume that cyberbullying is a natural thing.